The effect of fruit fly larval density on some quality parameters of mango - Akoto, S.H.; Billah, M.K.; Afreh-Nuamah, K.; Owusu, E.O. (Journal of Animal & Plant Sciences, 2011)
Three varieties of mango, Jaffna, Palmer and Kent were infested with different first instar larval densities (10, 20 and 30) of the invasive fruit fly species, Bactrocera invadens Drew, Tsuruta & White. This was to determine the effect of each of the densities on three fruit quality parameters. The parameters included Total Soluble Solids (TSS), Percentage Titratable Acidity (% T.A.) and pH, of which TSS and pH showed decreasing trends while % T.A. showed an increasing trend with time. In the controlled treatments where fruits were either held intact or punctured but with no introduction of larvae, there was an increase in pH and TSS and a decrease in %T.A.. The shelf-life, which was taken as the period from the first day of treatment till signs of damage were observed, saw the three varieties infested with 10 larvae lasting up to 6 days, while fruits infested with 20 and 30 larvae lasted for 3 days. The shelf life of the controlled treatments for all the varieties lasted till the 15th day. The presence of fruit fly larvae in fruits causes a number of changes in internal quality parameters such as the TSS, pH, % T.A. and the internal damage area. While pH and TSS decreased with storage time, % T.A. increased with storage time compared with the controlled fruits. Total damage area of fruits was also increased with increase number of larvae introduced. pH, TSS and % T.A. of Jaffna and Kent on the 3rd day of storage were almost the same as their control treatments. Despite the differences, the presence of fruit fly larvae in fruits (irrespective of number), will have negative impact on the internal quality parameters after the 3rd day of storage and reduce the market (export and locally) value of the fruits.
Keywords: Bactrocera invadens; larval infestation; Total soluble solid; Percentage titratable acidity; pH